The challenges and risk of laboratory handling on a histology specimen during COVID-19 pandemic - Mohd Fariz Amri; Nornazirah Azizan; Faezahtul Arbaeyah Hussain; Firdaus Hayati; Syed Sharizman Syed Abdul Rahim; Zahir Izuan Azhar (Elsevier Ltd, 2021)
The Coronavirus Disease 2019 (COVID-19) pandemic has taken the world into turmoil by surprise. The rapid spreading of this virus has led to an exponential increase in the number of cases. It has created a public health disaster, causing a collapse of the health system in every part of the world. Many sectors in the health area are affected, including histopathology services. The challenges and risk of viral transmission can come from various aspects and levels. For COVID-19 tests, there are even cases of no direct contact with the specimens; the specimens received infection from individuals of unknown status. The fixatives used for histopathology specimens are believed to be inactivated viruses, which can be an inactivate coronavirus. Even so, precautions have to be put in place to prevent the spread of infection to laboratory personnel, especially to those handling underfixed and fresh frozen cytology samples. Precautions must also be taken when dealing with histopathology services, by wearing full personal protective equipment and by executing other standard safety measures. The purpose of this review is to highlight the challenges faced in managing histopathology services in our centre during the COVID-19 pandemic.